2022
DOI: 10.1038/s41598-022-11370-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenies from unaligned proteomes using sequence environments of amino acid residues

Abstract: Alignment-free methods for sequence comparison and phylogeny inference have attracted a great deal of attention in recent years. Several algorithms have been implemented in diverse software packages. Despite the great number of existing methods, most of them are based on word statistics. Although they propose different filtering and weighting strategies and explore different metrics, their performance may be limited by the phylogenetic signal preserved in these words. Herein, we present a different approach ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Many authors (cf. Edwards et al 2002;Chan et al 2014;Balaban et al 2022;Van Etten et al 2023;Aledo 2022;Dylus et al 2023) declared that k-mers from unaligned data deliver good phylogenetic information, but our analysis shows that k-mers derived from unaligned sequences contain less information than sequences augmented with alignment information. We agree that unaligned data analysis is a great first and quick step to evaluate phylogenetic relationships, but if great accuracy is needed, then aligned sequences will be necessary.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Many authors (cf. Edwards et al 2002;Chan et al 2014;Balaban et al 2022;Van Etten et al 2023;Aledo 2022;Dylus et al 2023) declared that k-mers from unaligned data deliver good phylogenetic information, but our analysis shows that k-mers derived from unaligned sequences contain less information than sequences augmented with alignment information. We agree that unaligned data analysis is a great first and quick step to evaluate phylogenetic relationships, but if great accuracy is needed, then aligned sequences will be necessary.…”
Section: Discussionmentioning
confidence: 55%
“…For example, they can be used to derive distances to be summarized into phylogenies (Edwards et al 2002; Chan et al 2014; Balaban et al 2022; Van Etten et al 2023). Alignment-free approaches for phylogeny inference have attracted considerable attention in recent years (Dylus et al 2023; Aledo 2022; Bernard et al 2021; Zielezinski et al 2017). For example, several studies have shown that the alignment artifacts can significantly impact tree topology (Ogden and Rosenberg 2006; Wong et al 2008; Du et al 2019).…”
Section: Introductionmentioning
confidence: 99%